Beam Monitors for Tomorrow: The Challenges of Electron and Photon FLASH RT - Vignati, Anna; Giordanengo, Simona; Fausti, Federico; Martì Villarreal, Oscar A.; Mas Milian, Felix; Mazza, Giovanni; Shakarami, Zahra; Cirio, Roberto; Monaco, Vincenzo; Sacchi, Roberto (Frontiers in Physics, 2020)
The emergent FLASH RadioTherapy (RT) uses ultrahigh dose-rate irradiation (up to 107 Gy/s instantaneous dose-rate in each μs pulse) to deliver a single high dose of irradiation in a very short time (less than 200 milliseconds). Pre-clinical studies at ultrahigh dose-rates recently showed an increased ratio between tumoricidal effect and normal tissue toxicity (therapeutic index), compared to conventional RT at standard Gy/min dose-rates. If confirmed by biological in vivo validations, this could represent a breakthrough in cancer treatment. However, the reliability and the accuracy of experimental studies are nowadays limited by the lack of detectors able to measure online the beam fluence at FLASH dose-rates. The behaviour of standard beam monitors (gas-filled ionization chambers) is compromised by the volume recombination caused by the amount of charges created per unit volume and unit time, due to the large dose-rate. Moreover, due to the lack of proper monitoring devices and to the uncertainties of its future applications, very few facilities are able to deliver at present FLASH irradiations. In this contribution, we report about the physical and technological challenges of monitoring high and ultra-high dose-rates with electrons and photon beams, starting from the pre-clinical and clinical constraints for new devices. Based on the extensive experience in silicon detectors for monitoring applications in RT with external beams, the work then investigates silicon sensors as a possible option to tackle such extreme requirements and a rugged thin and large (e.g. 10×10 cm2) flat detector (silicon-based sensor + readout electronics) is therefore outlined. This study aims at presenting the FLASH-RT dosimetry problem and analysing the possibilities for a silicon sensor to be employed as sensing device for several FLASH scenarios, including some ideas on the readout part. However, more detailed simulations and studies are demanded to delineate more precisely the technical choices to be undertaken in order to tackle the clinical accuracy required on the beam fluence, typically a few %, during photon and electron high and ultra-high irradiations, the required minimal perturbation of the beam and the high level of radiation resistance.